HUBUNGAN STATUS GIZI, ASI EKSLUSIF DAN PAPARAN ASAP ROKOK DENGAN KEJADIAN ISPA BALITA - Evy Wisudariani; Soja Zusnita; Marta Butar Butar (JOURNAL HEALTH AND NUTRITIONS, 2022)
Acute Respiratory Infection Disease (ARI) is an acute infectious disease that attacks one or more respiratory organs caused by microorganisms that can last for 2 weeks. The purpose of this study was to determine the correlation between nutritional status, exclusive breastfeeding and smoking with the incidence of ARI in the working area of the Puskesmas Semerap, Kerinci Jambi Regency. This research is a quantitative study with a cross sectional approach with a proportional random sampling technique with a total sample of 106 children under five. Data collection was carried out in April 2022. The independent variable was the nutritional status of children under five, history of exclusive breastfeeding and exposure to cigaratte smoke and the dependent variable was ARI. Analysis using Chi Square and Cox Regression test. The proportion of the incidence of ARI in toddlers is 55.7%. There is correlation between nutritional status (undernutrition p= 0.046, PR= 3.13; over nutrition p= 0.014, PR= 3.67), history of exclusive breastfeeding (p= 0.029, PR= 1.51) and exposure to cigarette smoke ( p= 0.020, PR= 3). Factors that influence the incidence of ARI in infants are maternal knowledge, nutritional status, history of exclusive breastfeeding, exposure to cigarette smoke. t is hoped that the community, especially mothers of toddlers, always monitor the growth and development of toddlers by routine weighing, giving immunizations and complementary foods with balanced nutrition requirements.ISPA (Infeksi Saluran Pernapasan Akut) adalah penyakit infeksi akut yang menyerang satu atau lebih organ pernapasan yang disebabkan oleh mikroorganisme yang dapat berlangsung selama 2 minggu. Tujuan penelitian ini adalah untuk mengetahui hubungan status gizi, ASI ekslusif dan rokok dengan kejadian ISPA di wilayah kerja Puskesmas Semerap Kabupaten Kerinci Jambi. Penelitian ini adalah penelitian kuantitatif dengan pendekatan Cross Sectional dengan teknik Proportional Random Sampling dengan jumlah sampel 106 balita. Pengumpulan data dilakukan pada bulan April 2022. Variabel independen adalah status gizi balita, riwayat ASI eksklusif dan paparan asap rokok dan variable dependen adalah ISPA. Analisis menggunakan uji Chi Square dan Cox Regression. Proporsi kejadian ISPA pada balita sebanyak 55,7%. Terdapat hubungan antara status gizi (gizi kurang p= 0,046, PR= 3,13; gizi lebih p= 0,014, PR= 3,67), riwayat ASI eksklusif (p= 0,029, PR= 1,51) dan paparan asap rokok (p= 0,020, PR= 3). Faktor yang mempengaruhi kejadian ISPA pada balita adalah pengetahuan ibu, status gizi, riwayat ASI eksklusif, paparan asap rokok. Diharapkan kepada masyarakat, khususnya ibu balita agar selali memantau tumbuh kembang balita dengan penimbangan rutin, pemberian imunisasi dan makanan pendamping ASI yang syarat gizi seimbang.